Inertial Properties of the TE Waveguide Fields - Erden, Fatih; Tretyakov, Oleg A.; Cosan, Ahmet A. (Electromagnetics Acad, 2018)
Inertial properties of the TE-waveguide modal fields are studied in time-domain making use of an analytical method, named as evolutionary approach to electrodynamics (EAE). To achieve inertial characteristics, electric field vector with dimension of volt per meter and magnetic field vector with dimension of ampere per meter in Maxwell's equations are factorized in SI units to obtain new electric and magnetic field vectors with their common dimensions of inverse meter. Having the fields with the common dimensions makes them summable. Using EAE, modal basis elements that depend on transverse coordinates and modal amplitudes that depend on time and longitudinal coordinate are obtained by solving the boundary eigenvalue problem. As a result of using the new electric and magnetic field vectors, the energetic properties are derived as real-valued functions of coordinates and time. Then, the inertial properties (that is, electromagnetic mass and momentum) of the TE-waveguide modes are obtained as the functions of time.
Keywords: Klein-Gordon Equation; Modal Waves; Cavity; Modes